Neurosarcoidosis-associated central diabetes insipidus masked by adrenal insufficiency. (22nd January 2015) - Non, Lemuel; Brito, Daniel; Anastasopoulou, Catherine
Abstract : Central diabetes insipidus (CDI) is an infrequent complication of neurosarcoidosis (NS). Its presentation may be masked by adrenal insufficiency (AI) and uncovered by subsequent steroid replacement. A 45-year-old woman with a history of NS presented 2 weeks after abrupt cessation of prednisone with nausea, vomiting, decreased oral intake and confusion. She was diagnosed with secondary AI and intravenous hydrocortisone was promptly begun. Over the next few days, however, the patient developed severe thirst and polyuria exceeding 6 L of urine per day, accompanied by hypernatraemia and hypo-osmolar urine. She was presumed to have CDI due to NS, and intranasal desmopressin was administered. This eventually normalised her urine output and serum sodium. The patient was discharged improved on intranasal desmopressin and oral prednisone. AI may mask the manifestation of CDI because low serum cortisol impairs renal-free water clearance. Steroid replacement reverses this process and unmasks an underlying CDI.